Freedom of Speech and Religious Expression on Social Media Reviewed from the Perspective of Ethics and Islamic Law - Tampubolon, Ichwansyah; Kholidah, Kholidah (Pena Justisia: Media Komunikasi dan Kajian Hukum, 2024)
This article aims to describe freedom of speech and religious expression on social media from the perspective of Islamic ethics and law with a normative and descriptive approach. This study is in the form of a literature review using social media accounts, such as Facebook, Youtube, websites, and other references/lliterature as data sources. Theoretically, the state guarantees freedom of speech and religious expression for everyone on social media. However, freedom of speech and expression on social media must still take into account Islamic ethical values and obey the principles of applicable legal provisions. Preachers on social media continue to maintain and respect the right to freedom, both from speech/expression, words chosen, methods, attitudes, and behavior of delivery. This is intended so that the rights of others, freedom, and sanctity of religious symbols are not disturbed so that the welfare of the people in religious life is maintained.